The Cardiac Donor: Selection, Preoperative Care, and Organ Procurement and Preservation - Colón, Rolando (1987)
A successful cardiac transplant starts with the selection of an appropriate donor. Once consent to organ donation has been obtained, the donor should be managed aggressively in order to maintain optimal organ function. In the case of multi-organ donation, the heart is the first organ to be prepared, as well as the first to be removed. By means of simple preservation methods, the heart can be maintained for up to 4 hours ex vivo. For optimal timing and minimal ischemia, however, excellent communication and coordination is necessary on the part of transplant team members. (Texas Heart Institute Journal 1987; 14:359-363)